To study and compare effect of isoflurane and sevoflurane on adult patients postoperatively under general anesthesia by measure liver function test - Vinita Rawat; Gourab Bhaduri; Shreya Dhir; Sahil Yadav (Asian Journal of Medical Sciences, 2024)
Background: Effect of inhalational agents, namely, isoflurane and sevoflurane on patients having renal parameters has been explored quite often but the effect on liver function test has been rarely reviewed till date. Aims and Objectives: The aim of the study was to study the pre-operative liver function of patients who underwent general anesthesia by measuring their liver function test, post-operative effects of isoflurane, sevoflurane, and comparison. Materials and Methods: A total of 90 patients aged between 18 and 60 years who were further divided into two groups, that is, Group 1: (Isoflurane, n=45) and Group 2: (Sevoflurane, n=45) were included in the study. Results: The study comprised 51.1% of males and 48.9% of females, with similar distribution in either group (P>0.05). Comparison of various pre-operative parameters at 24, 48, and 72 h in isoflurane cases showed that bilirubin, serum glutamic oxaloacetic transaminase (SGOT), serum glutamic-pyruvic transaminase (SGPT), protein, albumin, globulin were found to be statistically significant but urea, creatinine, prothrombin time, and international normalized ratio were insignificant (P>0.05, NS). Comparison of pre-operative hemoglobin with that at 24, 48, and 72 h in isoflurane cases showed that mean isoflurane was 12.69±1.77 which was found to be nil within 24 h, 48 h, and 72 h. Comparison of various parameters at 24, 48, and 72 h in sevoflurane cases showed that pre-operative mean sevoflurane was 0.49±0.18 which was found to increase within 72 h, that is, 0.60±0.18. Similarly, SGOT was found increased from pre-operative 27.58±8.09 to 29.32±7.32, SGPT 23.29±7.02 to 26.22±6.81. Conclusion: Inhalation agent isoflurane and sevoflurane cause significant changes in patient’s liver function test, postoperatively under general anesthesia as indicated by various liver function parameters.